Increase Concentration of Transforming Growth Factor Beta (TGF-β) in Breast Milk of Mothers With Psychological Disorders - Shariat, Mamak; Abedinia, Nasrin; Rezaei, Nima; Farrokhzad, Nahid (Acta medica Iranica, 2017)
Several studies have shown an imbalance between proinflammatory and anti-inflammatory cytokines in depression and anxiety disorders. However, less attention has been paid to the role of cytokines in psychological disorder in mothers who breastfeed. This study looks at whether concentration levels of TGF-β2 are altered in anxious and depressive breastfeeding mothers. This study checked the concentration level of TGF-B2 in relation with psychological symptoms on 110 breastfeeding mothers; based on random sampling method with using of Beck Depression Inventory (BDI), General Health Questionnaire (GHQ) and Spielberger Stress Scale (STAI) in 2015 also TGF-β2 was measured in breast milk using ELISA. We used of Pearson Correlation Method, independent t-test and one-way analysis of variance (ANOVA) to analyze the data. Psychological symptoms (Anxiety and depression) showed positive correlation with TGF-Beta level in which relationships were significant (P=0.01). Psychological problems may be uniquely associated with the level of TGF-β in breast milk. More attention should be paid to the mental health of mothers during breastfeeding, and more research needs to be done in this subject to clarify the relationship between psychological variables with the level of TGF-β in breast milk.